The effect of etanercept on traditional metabolic risk factors for cardiovascular disease in patients with rheumatoid arthritis. Issue 12 (December 2016) - Deodhar, Atul; Bitman, Bojena; Yang, Yue; Collier, David
Abstract Patients with rheumatoid arthritis (RA) are at an increased risk of cardiovascular disease (CVD). Treatment with tumor necrosis factor inhibitors improves both joint symptoms associated with RA and also CVD risk. This exploratory analysis of a phase 4 study evaluated changes in metabolic risk factors in patients with RA treated with etanercept. Metabolic analytes were measured at baseline, week 12, and week 24 in patients enrolled in a randomized, double-blind, placebo-controlled study to evaluate the efficacy and safety of etanercept in moderately active RA. Patients received either placebo or etanercept 50 mg every week (QW) for 12 weeks, after which all patients received etanercept 50 mg QW through week 24. Levels of metabolic analytes were assessed in all patients, including patients with diabetes and hyperlipidemia, and described descriptively. A total of 210 patients were randomized, 104 to placebo and 106 to etanercept. There were no significant changes in metabolic risk factors from baseline to week 12 or 24 in all patients. Levels of metabolic analytes were similar in patients with diabetes and hyperlipidemia, with some exceptions; fasting glucose and fasting insulin decreased through week 12, and hemoglobin A1C decreased slightly through week 24 in patients with diabetes. Treatment with etanercept did not adversely affect levels of metabolic risk factors for CVD in patients with RA.